Qualitative properties of solutions of the Neumann problem for a higher-order quasilinear parabolic equation - Tedeev, A. F. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The property of localization of perturbations is proved for a solution of an initial boundary-value Neumann problem in a region D = Ω x,t > 0, where Ω is a region in R^n with a noncompact boundary.